Is Sukuk Market Efficient? Evidence from the Malaysian Sukuk Market - Nursilah Ahmad; Nor Haziah Hashim; Syazwani Abd Rahim (Universiti Sains Islam Malaysia, 2024)
Market efficiency in capital markets is used to explain the degree to which prices reflect all available and relevant information about the fundamental value of the securities to help investors make informed decisions. Sukuk are priced according to the value of the assets backing them. The aim of the paper is to measure market efficiency of three Malaysian sukuk indices namely Bloomberg AIBIM Bursa Malaysia Corporate Sukuk Index (AIBIM), Bloomberg Malaysian Sukuk Ex-MYR Index (EXMYR) and Malaysian Foreign Currency Sukuk Index (MFCSUKUK). Daily returns of the three sukuk indices are collected for the period of 2010 until 2015. The efficiency was measured using GARCH-in-Mean (GARCH-M) estimation to identify different types of sukuk market efficiency. The findings indicate that EX-MYR and MFCSUKUK indices display weak form efficient market behaviour while AIBIM falls under the inefficient category. The inefficient market signals that all public information might not be fully reflected in the price, hence there is room for bargaining process or prices could be under or over-valued. For industry players, sukuk structural inefficiencies and sectorial mispricing behavior create investment opportunities due to possible existence of excess profit. For policy makers, an extreme case of inefficient market leads to market failure and welfare loss.